Two Decades of Computing at the University of Belize - Garcia, David; Rabbani, Farshad (My University, 2022)
Computer science became a distinct academic discipline in the early 1950s. The first computer science degree program was founded in Belize around 45 years later, under the auspices of the nascent University College of Belize, which would subsequently become the University of Belize. We present a twenty-year synopsis of a degree program created in 1998 to build an undergraduate curriculum using the surge of computing in the country of Belize as a catalyst coupled with the recognition of the importance of computing for national development. The four-year undergraduate degree program has resulted in steady student enrolment over the past two decades featuring a female student population consistent with female enrolment in similar computer science programs globally. The study details the origins, development efforts, successes, challenges, and recommendations for the program's future development.
Keywords: computer science education; information technology education; computing degree program; curriculum; program outcomes